2021
DOI: 10.1002/pssa.202000735
|View full text |Cite
|
Sign up to set email alerts
|

Spin‐Coated Bismuth Vanadate Thin Film as an Alternative Electron Transport Layer for Light‐Emitting Diode Application

Abstract: This study describes the bismuth vanadate thin films (BVO) as an alternative electron transport layer for widely used LiF for the electron‐only device (EODs) application. The BVO thin film is spin‐coated on a glass substrate as a function of solution concentration. The X‐ray diffraction pattern of the film deposited from 10 × 10−3m (BVO1) to 150 × 10−3m (BVO4) solution concentration possesses the BiVO4 phase with a tetragonal structure, whereas the film deposited at 200 × 10−3m (BVO5) shows the Bi2V4O11 phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…We found that the anticipated TC hkl values of B‐2 and B‐1 photoanode films are textured along (040) and (112) planes with values of 1.4 and 1.09 (Figure S3c, Supporting Information), which proves that the increase in TC value facilitates the grain growth in fovorable planer direction and the decrease in grain boundries. [ 39,40 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the anticipated TC hkl values of B‐2 and B‐1 photoanode films are textured along (040) and (112) planes with values of 1.4 and 1.09 (Figure S3c, Supporting Information), which proves that the increase in TC value facilitates the grain growth in fovorable planer direction and the decrease in grain boundries. [ 39,40 ]…”
Section: Resultsmentioning
confidence: 99%
“…We found that the anticipated TC hkl values of B-2 and B-1 photoanode films are textured along (040) and ( 112) planes with values of 1.4 and 1.09 (Figure S3c, Supporting Information), which proves that the increase in TC value facilitates the grain growth in fovorable planer direction and the decrease in grain boundries. [39,40] Raman studies have been taken to analyze the microstructure and phase confirmation of B-1, B-2, B-4, and GB-4 photoanodes (Figure 1f ). Raman shift at 212, 325, 367, 644, 710, and 826 cm À1 in B-2, B-4, and GB-4 films assured ms-BiVO 4 crystalline phase.…”
Section: Structural Chemical and Electronic Studies Of Bivo 4 Photoan...mentioning
confidence: 99%